Konsep Bunga Anti Riba Dalam Persepektif Prinsip Ekonomi Islam pada Lembaga Keuangan Syariah - setiawan, Indra Setiawan; Yahya, Muchlis; Yahya, Imam; Sukendar, Sukendar (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
This study aims to compare the fundamental principles about interest conventional banks and analyze their implications for Islamic banking practices. The approach used is a comparative analysis between the fundamental principles of conventional banks and Islamic banks based on relevant literature. The analysis results indicate that conventional banks adopt an interest-based system as compensation for the use of money, while Islamic banks use profit-sharing principles in accordance with Sharia principles. Additionally, Islamic banks also impose limitations on the allocation of funds to businesses deemed incompatible with Sharia principles. This comparison reveals fundamental differences in the basic principles and banking practices between the two types of banks. Islamic banks emphasize justice and sustainable economic development, while conventional banks focus more on using interest as compensation for the use of money. Thus, Islamic banks offer alternatives that align with Islamic values and can contribute to inclusive and sustainable economies.